2015
DOI: 10.1186/s13068-015-0246-7
|View full text |Cite
|
Sign up to set email alerts
|

Uniconazole-induced starch accumulation in the bioenergy crop duckweed (Landoltia punctata) I: transcriptome analysis of the effects of uniconazole on chlorophyll and endogenous hormone biosynthesis

Abstract: BackgroundDuckweed is a novel aquatic bioenergy crop that is found ubiquitously throughout the world. Uniconazole plays an important role in improving crop production through the regulation of endogenous hormone levels. We found that a high quantity and quality of duckweed growth can be achieved by uniconazole application, although the mechanisms are unknown.ResultsThe fronds of Landoltia punctata were sprayed evenly with 800 mg/L uniconazole. The dry weight following treatment increased by 10% compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 60 publications
3
37
0
Order By: Relevance
“…Uniconazole is a triazole chemical that is used as a plant growth retardant. It is active on a wide range of plants and acts by inhibiting the production of gibberellins (Liu et al , ). In the present study, a colonization rate increase was observed in uncut colonized seedlings under 10 mg l −1 uniconazole treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uniconazole is a triazole chemical that is used as a plant growth retardant. It is active on a wide range of plants and acts by inhibiting the production of gibberellins (Liu et al , ). In the present study, a colonization rate increase was observed in uncut colonized seedlings under 10 mg l −1 uniconazole treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, how root‐tip cutting affects the colonization rate of the host plant by ectomycorrhizal fungi under greenhouse conditions remains unknown. Uniconazole is a well‐known plant growth regulator (Jiang et al , ; Jiang et al , ; He et al , ) that regulates plant endogenous hormone levels and gene expression (Sasaki et al , ; Liu et al , ). The morphology and biomass allocation of Salvia miltiorrhiza was reportedly altered by uniconazole (Gao et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The quantity (dry weigh basis) of carbohydrate, starch, crude protein, crude fibre and lipid has been reported in the ranges of 17.6-35 %, 21-38 %, 16-41.7 %, 8.8-15.6 % and 4.5-9 %, respectively, by various researchers [24,[39][40][41]. However, concentration of lipid and starch seems comparatively lower in duckweed as compared to other plant biomasses that can be further enhanced considerably through plant growth conditions manipulations (like pH, temperature and nutrient concentration in culture substrates) [24,40,[42][43][44][45]. The major constituents of carbohydrate in duckweed biomass are 20.3 % pectin (including galacturonan, xylogalacturonan, rhamnogalacturonan), 3.5 % hemicellulose (comprising xyloglucan and xylan) and 0.03 % phenolic compounds [46].…”
Section: Potential Of Duckweed Biomass In Renewable Energy Operationsmentioning
confidence: 99%
“…Plant growth regulators could improve the yield of duckweed starch for bioethanol production. 14 Liu et al 15 sprayed Landoltia punctata fronds with 800 mg L À1 uniconazole and found high starch accumulation, a dry-weight starch content of up to 48%.…”
Section: Introductionmentioning
confidence: 99%